This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Key 1. Problem: t 3 y + 4 t 2 y = et , I.C. y (1) = 0 ,t < Rearrange: y + 4 t y = et t 3 , so p = 4 t ,q = et t 3 . 2. μ = exp( Z 4 t dt ) = exp(4 log( t )) = t 4 . 3. Multiplied equation: D t ( t 4 y ) = tet so t 4 y = et (t1) + c 4. Using the initial condition: (1) 4 (0) = e (11) + c so c = 0 . 5. Final answer: y = et (t1) t 4 . 2...
View
Full Document
 Fall '09
 EdrayGoins
 Expression, The Final

Click to edit the document details